1998
DOI: 10.1002/(sici)1096-9861(19981221)402:3<402::aid-cne8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb development is altered in small-eye (Sey) mice

Abstract: Small-eye (Sey) is a spontaneous, semidominant murine mutation that results from a point mutation in the Pax-6 gene. Both the eyes and the olfactory system fail to develop in homozygotes and these animals die neonatally. Heterozygotes (Sey/+) have different degrees of eye abnormalities including decreased lens size and cataracts. In the present study, we examined whether one mutated allele of Pax-6 also affects olfactory system development. By 42 days of age, main olfactory bulb volume was significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 42 publications
2
38
1
1
Order By: Relevance
“…Expression of Pax6 marks at least three cell populations in and around the OB: VZ cells in the OB, OB neurons, and scattered cells in the anterior olfactory nuclei (AON) (Stoykova and Gruss, 1994;Dellovade et al, 1998;Lopez-Mascaraque and de Castro, 2002;Hack et al, 2005;Kohwi et al, 2005). Among these Pax6 ϩ cells, the Dlx1&2 Ϫ/Ϫ mutation appears to selectively eliminate the OB interneurons (Fig.…”
Section: Cјdј) Dlx1and2mentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of Pax6 marks at least three cell populations in and around the OB: VZ cells in the OB, OB neurons, and scattered cells in the anterior olfactory nuclei (AON) (Stoykova and Gruss, 1994;Dellovade et al, 1998;Lopez-Mascaraque and de Castro, 2002;Hack et al, 2005;Kohwi et al, 2005). Among these Pax6 ϩ cells, the Dlx1&2 Ϫ/Ϫ mutation appears to selectively eliminate the OB interneurons (Fig.…”
Section: Cјdј) Dlx1and2mentioning
confidence: 99%
“…In the absence of Dlx1&2, the mouse prenatal OB nearly lacks all expression of essential regulators of GABAergic function (glutamic acid decarboxylase and vesicular GABA transporter). Also, the OB mantle layer nearly lacks expression of several transcription factors, such as ER81, Pax6, and Sp8; these genes are either required or implicated in OB interneuron development (Dellovade et al, 1998;Stenman et al, 2003;Hack et al, 2005;Kohwi et al, 2005;Waclaw et al, 2006).…”
Section: Dlx1and2 and Mash1 Regulate Parallel Pathways In Ob Interneuromentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation studies of the neuronal progenitor cells also revealed the cell-autonomous requirements of Pax6 in differentiation of the dopaminergic PGCs (Kohwi et al 2005). Furthermore, the number of dopaminergic PGCs is decreased in Pax6 heterozygous mutant mice (Dellovade et al 1998;Kohwi et al 2005). We recently identified that the number of other PGC subtypes is also reduced in the olfactory bulb of Pax6 heterozygous mutant (H. Haba, T. Nomura and N. Osumi unpubl.…”
Section: Role Of Pax6 In the Generation Of Olfactory Bulb Interneuronsmentioning
confidence: 98%
“…Une protéine clé pour la génération des neurones dopaminergiques du cerveau antérieur est le facteur de transcription Pax6 (paired box 6) [4,5]. De plus, il a été montré que l'action de ce facteur est clairement dépendante de sa concentration, notamment dans sa fonction de déterminant dopaminergique [6]. Il doit donc nécessairement exister des méca-nismes qui régulent finement l'expression de cette protéine dans les cellules.…”
unclassified